Impact of amine functionalization on poly(furfuryl alcohol) properties - Delliere, Pierre; Antonczak, Pierre; Guigo, Nathanael (Polymer testing, 2023)
Polyfurfuryl alcohol (PFA) is a biobased thermoset with high stiffness. As carbonyls are formed via furan ring opening during polymerization, their inevitable presence was exploited to tune the PFA properties. Various diamines were employed to react with these carbonyls and consequence on thermal and mechanical properties were evaluated. Short and rigid diamines and long and flexible diamines were respectively selected for this functionalization. The more rigid amines lead to an increase of the Tg of the material compared to the pristine PFA but the ultimate properties were not particularly improved. Flexible polyetheramines such as Jeffamine D-2000 (J2000) combined with PFA allows the formation of a flexible elastomeric network (Tg = −44 °C) presenting high thermal stability due to the presence of the thermally stable furanic chains. For PFA/J2000 samples, a rigid crust is formed in oxidative conditions at T > 175 °C when the PFA content is relatively important (>50 % w/w). This phenomenon is massively impacting the ultimate mechanical properties and the thermal stability.